Noise Industrial Pollution: Health Vulnerabilities on Textile Industry Workers - Sumardiyono Sumardiyono; Reni Wijayanti; hartono hartono; Adi Heru Sutomo (Universitas Airlangga, 2019)
A safe and comfortable human life could be achieved by controlling the work environment so that the release of energy that is harmful to human health can be avoided. Noise often arises from an uncontrolled work environment and currently, more than 600 million people are exposed worldwide. Increased cortisol levels were one indicator stress-inducing of the occurrence of health effects because the worker's body is exposed to noise. If left longer it could increase sugar levels and cause diabetes mellitus. This study aims to analyze the effect of noise exposure on increasing blood cortisol levels and blood sugar levels in garment workers. This type of research was an analytic survey with a cross-sectional design. The respondents were chosen by using a stratified random sampling method and the total amount of respondents with a mean difference formula. As many as 75 people became respondents after being counted using the mean difference formula and chosen by the stratified random sampling method. The data were analyzed using ANOVA and Pearson Correlation. The results showed that respondents who exposed to noise above the threshold limit value had higher average blood cortisol levels compared to other respondents (p<0,000). Furthermore, an increase in blood cortisol levels was also positively correlated with an increase in blood sugar levels (r=0,898; p=0,000). Therefore, workers must be disciplined in using personal protective equipment.